Peran Strategi Manajemen Risiko dalam Meningkatkan Likuiditas dan Mengurangi Risiko Kredit di Sektor Perbankan Indonesia - Salwatul Muslimah; Rini Puji Astuti; Puput Dwi Wulandari; Salsabilah Aurani Faradilah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to examine how risk management techniques can reduce credit risk and increase liquidity in the Indonesian banking industry. It used quantitative methods and collected information from 130 banking professionals through a survey created on a Likert scale ranging from 1 to 5. The Structural Equation Modeling Partial Least Squares (SEM-PLS 3) approach was used to test the hypothesis. According to research, practicing efficient risk management techniques significantly lowers credit risk while increasing liquidity. The findings of this study emphasize the crucial importance of having a strong risk management framework due to its role in ensuring financial stability and enhancing the performance of the Indonesian banking sector. The conclusion of this study offers strategic benefits to banking institutions and policymakers in maximizing risk management procedures in the face of shifting economic conditions.